AVALIAÇÃO DA FLOTAÇÃO E DA SEDIMENTAÇÃO NO PÓS-TRATAMENTO DE EFLUENTE DE REATOR ANAERÓBIO VISANDO REMOÇÃO DE FÓSFORO - Kuhn, Daiane Cristine (2019)
The effluent from anaerobic reactor usually doesn’t present sufficient quality to meet the discharge and quality standards recommended in the brazilian environmental legislation, because they’re inefficient in the removal of nutrients such as phosphorus and nitrogen, organic matter, solids and pathogens. Excessive nutrient inputs are a major cause of water eutrophication. The present research had as objective to evaluate the dissol and theved air flotation sedimentation in the post-treatment of anaerobic reactor effluents aiming at the removal of phosphorus on a bench scale (flotateste). In the first step, the FeCl3 (0, 50 and 100 mg.L-1) and flotation rates (5, 8 and 15 cm/min) in dissolved air flotation were analyzed, and the FeCl3 dosages (0, 50 and 100 mg.L-1) and sedimentation time (30, 45 and 60 minutes) in the sedimentation by factorial design of experiments, with total phosphorus, soluble phosphorus, total COD, soluble COD and turbidity as response variables. The second stage comprised the evaluation of the optimum values found from the application of the same in the post-treatment of effluents presenting the best removal efficiency of the parameters studied. Further, Daphnia magna toxicity tests and centrifugation tests were performed with the sludge from the post-treatments. The concentration of 100 mg.L-1 of FeCl3 was more effective in the two types of post-treatment, with removal efficiencies of 80,8%, 93%, of total phosphorus and soluble phosphorus, respectively, in DAF. In sedimentation, removal efficiencies of 96,7% and 96,5% of total phosphorus and soluble phosphorus were obtained, respectively. In the centrifugation test, with sludge from the post-treatment by DAF, the highest solids content in the pie was obtained, of 30,3%. As for the toxicity tests with Daphnia magna, the UASB reactor effluent showed to be toxic (TF = 4). The post-treatment effluents by DAF and sedimentation aren’t considered to be toxic (TF = 1).